Photodiode-based time zero determination for ultrafast electron microscopy - S. T. Kempers; S. Borrelli; E. R. Kieft; H. A. van Doorn; P. H. A. Mutsaers; O. J. Luiten (Structural Dynamics, 2023)
Pump-probe experiments in ultrafast electron microscopy require temporal overlap between the pump and probe pulses. Accurate measurements of the time delay between them allows for the determination of the time zero, the moment in time where both pulses perfectly overlap. In this work, we present the use of a photodiode-based alignment method for these time zero measurements. The cheap and easy-to-use device consists of a photodiode in a sample holder and enables us to temporally align individual, single-electron pulses with femtosecond laser pulses. In a first device, a temporal resolution of 24 ps is obtained, limited by the photodiode design. Future work will utilize a smaller photodiode with a lower capacitance, which will increase the temporal resolution and add spatial resolution as well. This upgrade will bring the method toward the micrometer and picosecond spatiotemporal resolution.